Burden and contributing factors to overweight and obesity in young adolescents in Addis Ababa, Ethiopia - Roisin E. Drysdale; Amare W. Tadesse; Alemayehu Worku; Hanna Y. Berhane; Sachin Shinde; Isabel Madzorera; Deepika Sharma; Wafaie W. Fawzi (Maternal and Child Nutrition)
Abstract The prevalence of overweight/obesity in adolescents has increased globally, including in low‐ and middle‐income countries. Early adolescence provides an opportunity to develop and encourage positive health and behavioural practices, yet it is an understudied age group with limited information to guide and inform appropriate interventions. This study aims to determine the prevalence of overweight/obesity in young adolescents, aged between 10 and 14 years attending public schools in Addis Ababa, Ethiopia, and to explore the contributing factors. A cross‐sectional school‐based study was conducted. Adolescents completed individual questionnaires. Weight (kg) and height (m) measurements were converted to BMI‐for‐age and gender z‐scores. Multivariate regression analysis was conducted to determine the associated factors. The overall prevalence of overweight/obesity was 8% among adolescents aged 10–14 years and it was significantly higher in females (13%) than males (2%). The diet quality for the majority of the adolescents was inadequate, putting them at risk for poor health outcomes. The contributors to overweight/obesity were different between males and females. Age and no access to a flush toilet were negatively associated with overweight/obesity in males and access to a computer, laptop or tablet was positively associated. In females, menarche was positively associated with overweight/obesity. Living with only their mother or another female adult and an increase in physical activity were negatively associated with overweight/obesity. There is a need to improve the diet quality of young adolescents in Ethiopia and understand the reasons why females are less physically active to limit the risk of poor diet‐related health outcomes.